BASIS OF JUDES AT THE LEVELAGAINST THE PERSONNEL OF THE CRIMINAL ACTION OF RAPE UNDER THE AGE OF CHILDREN CONTINOUSLY - Danti Yudistiara; Budi Santoso (PRANATA HUKUM, 2023)
There is an appeal filed by the Public Prosecutor against the decision of the Blambangan Umpu District Court Number: 81/Pid.Sus/2021/PN Bbu, Decision regarding the criminal act of rape which was carried out continuously with underage victims. The decision of the Blambangan Umpu District Court was carried out as a continuation of the submission of a letter of cassation from the Way Kanan District Attorney who felt that he did not fulfill the value of justice in passing a decision on the period of detention to investigators . defendant. In this article, what will be discussed is: what are the factors that cause the defendant to commit the crime of rape against a minor and what is the basis for judges' considerations at the appellate level in making decisions on criminal cases against children that are carried out continuously. This research uses a normative and empirical juridical research method, using secondary and primary data, obtained from library research and field studies, and data analysis with qualitative juridical analysis. The results of the study show that thefactors that cause the defendant to commit the crime of rape of a minor which is carried out continuously are environmental factors that provide opportunities to commit crimes. Basic considerations of judges at the appellate level in cases of rape of minors which are carried out continuously by taking into account the guidelines for sentencing regarding the degree of guilt of the accused, the impact of the crime and the value of the sentence. assets obtained by the defendant from the crime and the aggravating and mitigating laws and regulations.